Advances in Rehabilitation of Hearing Loss - Zanetti, Diego; Di Berardino, Federica (IntechOpen, 2020)
This book covers some innovative aspects of the multifaceted and continuously evolving field of rehabilitation of hearing loss. International leading experts share their view and advanced experience on unilateral deafness, services for the hard of hearing, hair cell regeneration, advanced imaging, active middle ear and bone conduction hearing aids, and cochlear implants.